2020
DOI: 10.1101/2020.04.20.050450
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cold adaptation drives population genomic divergence in the ecological specialist,Drosophila montana

Abstract: 3 6 9 12 15 ABSTRACT Detecting signatures of ecological adaptation in comparative genomics is challenging, but analysing population samples with characterised geographic distributions, such as clinal variation, can help identify genes showing covariation with important ecological variation. Here we analysed patterns of geographic variation in the cold-adapted species Drosophila montana across phenotypes, genotypes and environmental conditions and searched for signatures of cold adaptation inpopulations' genomi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 92 publications
(138 reference statements)
1
16
0
Order By: Relevance
“…Latitudinal variation in CCRT, but not in CTmin, has also been observed in two widespread ant species, Myrmica rubra and Myrmica ruginodis [29]. Although it is possible that the low variation in cold tolerance in our study is a consequence of relatively low number of studied strains or populations, a recent study found similar trends when using mass-bred D. montana populations for a limited number of places from North America [89].…”
Section: Effects Of Latitude and Bioclimatic Variables On Fly Cold Tolerance Vary Even Between Closely-related Speciessupporting
confidence: 72%
See 1 more Smart Citation
“…Latitudinal variation in CCRT, but not in CTmin, has also been observed in two widespread ant species, Myrmica rubra and Myrmica ruginodis [29]. Although it is possible that the low variation in cold tolerance in our study is a consequence of relatively low number of studied strains or populations, a recent study found similar trends when using mass-bred D. montana populations for a limited number of places from North America [89].…”
Section: Effects Of Latitude and Bioclimatic Variables On Fly Cold Tolerance Vary Even Between Closely-related Speciessupporting
confidence: 72%
“…The candidate gene D. virilis species group shows several distinct features in their circadian clock system compared to D. melanogaster, which has enabled their adaptation in high-latitudes [72][73][74]. Interestingly, vrille was the only core circadian clock gene that was found to show both population-level differentiation in clinal cold tolerance study [89] as well as expression level differences when cold-acclimated and non-acclimated D. montana flies were compared [77]. This gene was also one of the differentially expressed genes in our earlier microarray study investigating cold tolerance of D. montana and D. virilis [65].…”
Section: Investigating Circadian Clock Gene Vrille and Its Effects On Fly Cold Tolerance Using Sequence Variation And Rna Interference (Rmentioning
confidence: 99%
“…Insect species with a wide distribution offer a great opportunity to trace latitudinal variation in traits that are important in reproduction and stress tolerances, and particularly in the contribution of circadian clock(s) and/or PPTM in their regulation. Our study species, D. montana , shows steep latitudinal clines in CDL and its temperature-sensitivity ( Tyukmaeva et al, 2020 ), as well as in the flies’ basal cold tolerance ( Wiberg et al, 2020 ). In the present study, variation in the diapause proportions of D. montana cline strains, and the control and selection lines, in extra long and short photoperiods revealed many interesting aspects of PPTM related to our study questions.…”
Section: Discussionmentioning
confidence: 86%
“…Also morphological differences, particularly in body pigmentation, have been documented in this group, though the evolutionary processes underpinning pigmentation differences is not yet well understood (Wittkopp et al 2002, Wittkopp et al 2002; Kulikov et al 2004; Bubliy et al 2007; Ahmed-Braimah and Sweigart 2015; Lamb et al 2020). Several species of the virilis group, especially those of the montana phylad, persist in extreme cold environments, and show high cold acclimation and diapause which may contribute to genomic divergence (Vesala et al 2012; Parker et al 2015, 2016; Salminen et al 2015; Tyukmaeva et al 2015; Wiberg et al 2021). Fixed and polymorphic chromosomal inversions have been reported within the group and may be driven by the activity and expansion of transposable elements, giving rise to regions of high differentiation between species and populations (Evgen’ev et al 2000; Fonseca et al 2013; Reis et al 2018).…”
Section: Introductionmentioning
confidence: 99%